ANALYSIS OF THE INFLUENCE OF DORNIC ACIDITY AND PASTEURIZATION ON THE CALORIC VALUE OF HUMAN MILK. (CIPEEX, 2026)
INTRODUCTION: The pasteurization of human milk, although essential for microbiological safety, may affect its caloric value. Evaluating this influence, in association with Dornic acidity, is crucial to ensure the nutritional quality of the milk provided by human milk banks. OBJECTIVE: To analyze the impacts of Dornic acidity and pasteurization on the crematocrit of human milk. MATERIALS AND METHODS: A total of 179 human milk samples were analyzed, collected from a Human Milk Bank in Goiás, Brazil. Dornic acidity and crematocrit data were evaluated using descriptive and inferential statistical tests, including Cohen’s d test. Additionally, linear regression analysis was conducted to assess the relationship between Dornic acidity and changes in crematocrit. RESULTS: Pasteurization resulted in an average loss of 28.66 Kcal/L. The caloric classification of the samples revealed that 36% became hypocaloric after pasteurization. Linear regression analysis indicated that Dornic acidity had no statistically significant effect on post-pasteurization crematocrit variation (R² = 0.01, p-value = 0.1709). CONCLUSION: In this study, pasteurization reduced the crematocrit by 4.81%, lower than the 18% reported in the literature. Therefore, pasteurization decreases the caloric density of human milk, but with a relatively low impact. Regarding Dornic acidity, no significant correlation was found with changes in caloric value.
Keywords: Acidity.; Human Milk Banks; Human Milk; Pasteurization